2009
DOI: 10.1088/0953-8984/21/22/225001
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of benzene, phenol, propane and carbonic acid molecules on oxidized Al(111) and α- Al2O3(0001) surfaces: a first-principles study

Abstract: We present the results of ab initio calculations describing the adsorption of certain small organic molecules on clean and oxidized Al(111) surfaces as well as on the α- Al(2)O(3)(0001) surface. Our results show that adsorption of benzene on the clean and oxidized Al(111) surfaces is generally weak, the adsorption energy being at most around -0.5 eV per benzene molecule, and the molecule adsorbed at a considerable distance from the surfaces. The adsorption energy varies weakly at the different adsorption sites… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
4
12
0
Order By: Relevance
“…The molecule has extensively been studied both experimentally [1][2][3][4][5][6] and computationally [6][7][8][9][10][11] . The interaction of BPA-PC or its chemical groups, phenylene, carbonate, and isopropylidene, with crystal surfaces has also been studied, and they provide a good model system for studying the properties of surfaces and interfaces 8,[11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The molecule has extensively been studied both experimentally [1][2][3][4][5][6] and computationally [6][7][8][9][10][11] . The interaction of BPA-PC or its chemical groups, phenylene, carbonate, and isopropylidene, with crystal surfaces has also been studied, and they provide a good model system for studying the properties of surfaces and interfaces 8,[11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%
“…In this work we extend a subset of our previous DFT calculations for the groups of BPA-PC (Ref. 12 ) by taking into account the interactions of nearest-neighbor groups as well as the vdW interactions. Both of these factors can be crucial in understanding the adsorption processes of large molecules, with macromolecules (polymers) being an extreme example.…”
mentioning
confidence: 99%
“…Hence, the energetic barrier for Al desorption is considerably higher than that for Mg, indicating the formation of stronger bonds between an Al adatom and underlying intermetallic Mg 2 Ca compared to a Mg adatom. In comparison, the desorption energy of Al on a Mg 2 Ca nanocluster lies in the range of O desorption from fcc Al(111), which has been reported to require 7.3 eV/atom [28]. Consequently, our calculations suggest that Al is preferably incorporated into the intermetallic (Mg,Al) 2 Ca phases.…”
Section: Resultsmentioning
confidence: 63%
“…A DFT study of adsorption of these molecules on aluminium found similar results to the case of nickel 4 although the adsorption energy on aluminium is lower than for nickel.…”
Section: Introductionmentioning
confidence: 55%